Squeak the lion - Sully, Katherine; Leach, Emma (Alligator Books London, 2011)
Squeak the Lion wants to be just like his older brothers. He hates being the baby of the pride. Even his name is a baby name. No one calls him by his real name - Rory. One day while out hunting Squeak's brother Bruno runs into trouble. Only fast thinking and strength can help as the elephants thunder nearer